DESKRIPSI DAN EKSPLORASI TEKNIK PERMAINAN DAN PENULISAN KARYA GAVOTTE AND RONDEAU KARYA JOHANN SEBASTIAN BACH - Gulo, Rizki Sozanolo; Manalu, Kartini (Jurnal Suluh Pendidikan, 2025)
This study discusses the interpretation and writing techniques of Johann Sebastian Bach's Gavotte and Rondeau. The techniques used are interpretation techniques based on musical elements such as dynamics, tempo, and playing techniques in the form of Speed, Power, Trill, Slur, Bare, Vibrato, Slide, Apoyando, and Tirando techniques. This study also explains the difficulties experienced by the author when presenting Gavotte and Rondeau in a recital exam and how to overcome them during the practice process. The very basic level of complexity in this Gavotte and Rondeau is aligning the tempo with the speed of hand movement and the articulation of the notes played.